e-Government for good governance : establishing efficient governance through data-driven policymaking in Africa - Ilori, Oluwatomiwa (University of Pretoria, 2023)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.